Image quality of low-radiation dose left atrial CT using filtered back projection and an iterative reconstruction algorithm: intra-individual comparison in unselected patients undergoing pulmonary vein isolation. (February 2018) - Fahlenkamp, Ute Lina; Diaz Ramirez, Ivan; Wagner, Moritz; Schwenke, Carsten; Huppertz, Alexander; Hamm, Bernd; Lembcke, Alexander
Background: Computed tomography (CT) of the left atrium (LA) is performed prior to pulmonary vein isolation (PVI) to improve success of circumferential ablation for atrial fibrillation. The ablation procedure itself exposes patients to substantial radiation doses, therefore radiation dose reduction in pre-ablational imaging is of concern. Purpose: To assess and compare diagnostic performance of low-radiation dose preprocedural CT in patients scheduled for PVI using two types of reconstruction algorithms. Material and Methods: Forty-six patients (61 ± 10 years) scheduled for PVI were enrolled in this study irrespective of body-mass-index or cardiac rhythm at examination. An electrocardiographically triggered dual-source CT scan was performed. Filtered back projection (FBP) and iterative reconstruction (IR) algorithms were applied. Images were integrated into an electroanatomic mapping (EAM) system. Subjective image quality was scored independently by two readers on a five-point scale for both reconstruction algorithms (1 = excellent to 5 = non-diagnostic). Signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), and effective radiation dose were calculated. Results: Data acquisition and EAM integration were successful in all patients. Median image quality score was 1 for both FBP (quartiles = 1, 1.62; range = 1–3) and IR (quartiles = 1, 1.5; range = 1–3). Mean SNR was 7.61 ± 2.14 for FBP and 9.02 ± 2.69 for IR. Mean CNR was 5.92 ± 1.80 for FBP and 6.95 ± 2.29 for IR. Mean effective radiation dose was 0.3 ± 0.1 mSv. Conclusion: At a radiation dose of 0.3 ± 0.1 mSv, high-pitch dual-source CT yields LA images of consistently high quality using both FBP and IR. IR raises SNR and CNR without significantly improving subjective image quality.